2013
DOI: 10.1016/j.wear.2012.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Wear of nano-structured carbide-free bainitic steels under dry rolling–sliding conditions

Abstract: Specially designed steels with carbon contents from 0.6 to 1.0 wt.% were isothermally transformed at very low temperatures, between 220 and 270°C, in order to obtain a nano-structured bainitic microstructure. It is shown that the wear resistance in dry rolling-sliding of these nano-structured steels is significantly superior to that of bainitic steels transformed at higher temperatures with similar hardness values. In addition to the highly refined microstructure, the transformation under strain to martensite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 23 publications
4
86
2
2
Order By: Relevance
“…A similar conclusion was reached when comparing the bulk form of the nanostructured bainite, which again had a lower sliding wear-rate than harder martensite [7]. The dry rolling-sliding wear of series of steels said to contain carbide-free bainite has been reported recently [8] ( a high slip of ∼ 5% was used in the test programme); here, the carbide-free bainitic steels were shown to exhibit significantly lower rates of wear (∼ 50%) than a steel with a lower bainitic microstructure, even at similar hardness levels and this was attributed to the desirable combination of hardness and toughness of the carbide-free bainitic microstructure. However, the metallography reported is not of sufficient resolution to establish the presence of a nanostructure, and the higher transformation temperatures used are consistent with coarser forms of bainite.…”
Section: Introductionsupporting
confidence: 70%
“…A similar conclusion was reached when comparing the bulk form of the nanostructured bainite, which again had a lower sliding wear-rate than harder martensite [7]. The dry rolling-sliding wear of series of steels said to contain carbide-free bainite has been reported recently [8] ( a high slip of ∼ 5% was used in the test programme); here, the carbide-free bainitic steels were shown to exhibit significantly lower rates of wear (∼ 50%) than a steel with a lower bainitic microstructure, even at similar hardness levels and this was attributed to the desirable combination of hardness and toughness of the carbide-free bainitic microstructure. However, the metallography reported is not of sufficient resolution to establish the presence of a nanostructure, and the higher transformation temperatures used are consistent with coarser forms of bainite.…”
Section: Introductionsupporting
confidence: 70%
“…Recently, in the frame of a Research Fund for Coal and Steel (RFCS) project [9], these microstructures demonstrated superior potential for abrasive wear applications in large components, where a uniform microstructure free from residual stresses or without complex processing is required. Likewise, it was confirmed through industrial testing, that these new grades are on a par with significantly more expensive abrasive wear-resistant alloy steels [10].…”
Section: Nanostructured Bainitementioning
confidence: 85%
“…Bainite plate thickness and retained austenite content are shown to be important factors in controlling the yield strength, though additional, non-negligible parameters remain to be quantified [12]. Rolling-sliding wear performances are found to be exceptional, with as little as 1% of the specific wear rate of conventional 100Cr6 isothermally transformed to bainite [13]. It is suggested that this results from the decomposition of retained austenite in the worn layer, which considerably increases hardness and presumably introduces compressive residual stresses.…”
Section: Developing Nanocrystalline Steels By Displacive Reactionmentioning
confidence: 99%